Students as Producers: A Case Study of Technology-Based Projects - Cecilia Titiek Murniati; Ridwan Sanjaya (Soegijapranata Catholic University, 2017)
The existent literature on the integration of technology in language classrooms has addressed the issues of effective teaching strategies, the types of technologies students use, and teachers’ preparedness in adopting technology for the classrooms. Some scholars argue that the effectiveness of technology largely relies on the teaching strategies that teachers utilize. The findings of some studies shed light on the impact of technology on students’ attitude and engagement. Despite the unresolved debates about the use of technology in the classroom and its impact on student learning, the author’s current projects using games, YouTube, blog, and microblogging services indicated that students benefit from the projects in several ways. The participants of this study were students in the English Department in a private university in Semarang. The data for this study were collected from interviews, observation, and students’ learning reflective journals that students submitted upon the completion of the projects. The findings indicated that students felt more confident in applying their knowledge in real life situations. Interactions with teachers and peers, bridged by technology, contribute to their development as the creator of knowledge.